Features of the functioning of the innate and adaptive immunity system in patients with COVID-19 of the older age group - O. N. Scheglovitova; L. V. Kolobukhina; A. A. Babayants; I. S. Frolova; E. I. Isaeva; I. S. Kruzhkova; A. A. Samkov; N. A. Antipyat; I. N. Tyurin; A. N. Narovliansky; F. I. Ershov (Журнал инфектологии)
Goal. Characteristics of innate, cellular and adaptive immunity in patients of the older age group with COVID19.Materials and methods. Blood leukocytes were induced by Newcastle disease virus (α-interferon), phytohemagglutinin (γ-interferon), SARS CoV 2: RBD antigens and S-protein; interferon activity in human fibroblast culture and enzyme immunoassay were evaluated. In serum, IgG antibodies to SARS CoV2 and autoantibodies to interferon and to the endothelium of blood vessels were determined using a mono-layer of human umbilical vein cells. Statistical processing was performed in Excel 2016.Results. A decrease in the production of  α-interferon and γ-interferon was revealed: 1 week -74.2±15.1; 3 week-144.0±35.7 (p=0.01); control – 266.6 ±82 (relative to 3 weeks p=0.004) and IFN γ: 1 week -6.8±2; 3 week – 14.4 ±3.5 (p=0.03); control – 28.87.15 (relative to 3 weeks (p=0.007). Decreased production of γ-interferon by leukocytes of patients with induction by SARS CoV2 RBD and S-trimer anti-gens was revealed. Antibodies to SARS CoV2 were detected starting from the 2nd week of the disease, a large spread of indicators was noted. Autoantibodies to α2-interferon and to vascular surface antigens were detected.Conclusion. The state of innate immunity in patients of the older age group with severe and moderate COVID-19 was characterized by a decrease in the activity of the interferon system. Decreased activity of cellular immunity to SARS CoV2 antigens was noted. Adaptive immunity was characterized by the development of an imbalance in the form of the appearance of autoantibodies to α-interferon and vascular endothelium.